Early life exposures and development of allergic disease in infants with familial risk: Results from ongoing probiotic intervention trials. (25th August 2022) - Puisto, Reetta; Turta, Olli; Rautava, Samuli; Isolauri, Erika
Abstract: Aim: We search revision of risk determinants of the ongoing allergy epidemic. Methods: Children numbering 433 born to mothers with allergic disease or sensitisation were selected from the three ongoing probiotic intervention trials for this case–control study. Children who developed atopic eczema or food allergy, had positive skinprick test results or had been prescribed inhaled corticosteroids by the age of 2 years were identified as cases ( n = 231), while children without allergic manifestations were the healthy controls ( n = 202). The data on early environmental exposures were collected from prospectively documented study records. The statistical analyses were adjusted for potential confounders. Results: Determinants associated with the increased risk of atopic eczema were lower maternal prepregnancy BMI (aOR 0.15, 95% CI: 0.037–0.54) and maternal intrapartum antibiotic treatment (aOR 2.21, 95% CI 1.20–4.10), the latter also linked to obstructive respiratory symptoms (aOR 3.87, 95% CI 1.07–14.06). The risk of allergic sensitisation was associated with lower maternal prepegnancy BMI (aOR 0.18, 95% CI 0.43–0.79) and intrapartum antibiotic treatment (aOR 2.13, 95% CI 1.07–4.22). Conclusion: Based on our demonstrations, interventions such as personalised diets, can be optimised for specific subgroups and definite risk periods.